A combined electron backscattered diffraction and visco-plastic self-consistent analysis on the anisotropic deformation behavior in a Mg-Gd-Y alloy. (15th May 2017) - Sun, Jie; Jin, Li; Dong, Shuai; Dong, Jie; Zhang, Zhenyan; Wang, Fenghua; Ding, Wenjiang; Luo, Alan A.
Abstract: The anisotropic mechanical properties of Mg alloys are critical in the application. In this paper, the anisotropic deformation behavior of extruded and aged Mg-Gd-Y alloys was studied by using electron backscatter diffraction (EBSD) analysis and visco-plastic self-consistent (VPSC) modeling. The results show that the activation of extension twinning was not the main reason for the mechanical anisotropy in the extruded Mg-Gd-Y alloy. Because twinning activity is very low during deformation. VPSC results show that the anisotropic deformation behavior in the extruded Mg-Gd-Y alloy is caused by various behavior of slip activity. The higher strength in sample during tension along transversal direction (TD) is caused by the more activation of prismatic slip. Furthermore, β' precipitates in the aged Mg-Gd-Y alloy can inhibit basal slip effectively. The CRSS of basal slip (90 MPa) is very close to that of prismatic slip (100 MPa) which leads to a better strength symmetry in Mg-Gd-Y alloy after aging treatment. Graphical abstract: Highlights: Twinning activity is not the main reason for mechanical anisotropy in Mg-Gd-Y alloy. Mechanical anisotropy is controlled by various slip activity. The precipitates can improve mechanical symmetry.